A systems engineering–based approach for framing reliability, availability, and maintainability: A case study for subsea design. Issue 6 (23rd July 2018) - Zhang, Juntao; Haskins, Cecilia; Liu, Yiliu; Lundteigen, Mary Ann
Abstract: Framing reliability, availability and maintainability (RAM) aspects are critical for an engineering design, as RAM is concerned with the sustained capability of a system throughout its useful life. RAM analysts are responsible to consider both functional and dysfunctional behavior of a given system beyond the perspective of system designer. However, the system concept baseline developed by RAM toolset is often a partial view, which is either too abstract when preparing RAM analysis or too overloaded when integrating RAM analysis with design process. Such practice may not give systemic insights of the design concept, considering specific subsea design challenges such as limited accessibility and requirement for automate control. For this reason, it is of great importance to ensure an effective and sufficient communication between the domain of design and domain of RAM. Integrating with a well‐known engineering discipline, such as systems engineering (SE), may help analysts to create the collaborative design environment necessary to control the design risks for a system with high complexity. This article proposes a new framework that links SE with RAM engineering by connecting relevant concepts and models used. A novel subsea design concept is offered as a case study to demonstrate the key changes in subsea design activities for addressing RAM with the proposed framework.